2015
DOI: 10.1111/johs.12095
|View full text |Cite
|
Sign up to set email alerts
|

The Paranoid Style Revisited: Pseudo‐Conservatism in the 21st Century

Abstract: Fifty years ago, the Pulitzer Prize-winning historian Richard Hofstadter published the seminal essay, "The Paranoid Style in American Politics." In this and related works he examined the rhetoric animating the extreme right-wing of the country's electorate. In this article I revisit Hofstadter's claims regarding the marginalization of the paranoid style and its connection to status-based politics. A review of the most popular "pseudo-conservative" commentators, survey data, the rise of the Tea Party, and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Hofstadter gave numerous examples of this style from the history of his own country (for example, panics about the activities of the Illuminati in the 18 th century and about the Freemasons in the 19 th ) but noted that it is not monopolised by any particular nation nor any particular political ideology. This style is, arguably, still discernible in modern political discourse but communism no longer figures prominently amongst the threats to our way of life, which Appelrouth [ 2 ] now suggests “come in a variety of forms, some old, some new: ‘Islamofascists’, homosexuals, liberals, illegal aliens, feminists, the mainstream media”.…”
Section: Introductionmentioning
confidence: 99%
“…Hofstadter gave numerous examples of this style from the history of his own country (for example, panics about the activities of the Illuminati in the 18 th century and about the Freemasons in the 19 th ) but noted that it is not monopolised by any particular nation nor any particular political ideology. This style is, arguably, still discernible in modern political discourse but communism no longer figures prominently amongst the threats to our way of life, which Appelrouth [ 2 ] now suggests “come in a variety of forms, some old, some new: ‘Islamofascists’, homosexuals, liberals, illegal aliens, feminists, the mainstream media”.…”
Section: Introductionmentioning
confidence: 99%
“…While some argue that conspiracy theories are a necessary part of holding those in power accountable (see Basham, 2003;Dentith, 2016aDentith, , 2016bDentith & Orr, 2017) others argue that this is outweighed by their negative impact. Conspiracy theory belief is associated with reduced engagement with mainstream politics (Jolley & Douglas, 2014a), increased support for political violence and extremism (Bartlett & Miller, 2010;Imhoff et al, 2020;Uscinski & Parent, 2014), far-right activism (Appelrouth, 2017;Hofstadter, 1964;Sunstein & Vermule, 2009), and increased prejudice towards minority groups (Jolley, Meleady, & Douglas, 2020;Kofta et al, 2020). In public health, conspiracy theory belief is associated with reduced contraceptive use (Bogart & Thorburn, 2005), reduced intention to vaccinate (Jolley & Douglas, 2014b), avoidance of mainstream medicine (Lamberty & Imhoff, 2018;Oliver & Wood, 2014), reduced trust in medical experts (Oliver & Wood, ibid) and is a significant obstacle to constructive public responses to pandemics (Romer & Jamieson, 2020;Van Bavel et al, 2020).…”
Section: Defining Conspiracy Theoriesmentioning
confidence: 99%
“…Many political scientists agree that conspiracy theories are a political myth (Girardet 1986; Giry 2015a), a global vision of the world that can espouse different kinds of ideologies even though they have, in democratic countries at least, affinities with government distrust (Moore 2017), extremism (Bronner 2009;Bartlett, Miller 2010), populism (Bergmann 2018; see also Chapter 3.6 in this volume) and far-right activism (Hofstadter 1964;Sunstein, Vermeule 2009;Appelrouth 2017). More generally speaking, in terms of affiliation, political scientists have found that people are more likely to believe in conspiracy theories when they feel involved, when they tend to exonerate them or the group they belong to (Waters 1997;Russell et al 2011;Frampton et al 2016) and when they implicate their political opponents (Oliver, Wood 2014;Uscinski, Parent 2014).…”
Section: Main Findings and Debates: What Political Scientists Know An...mentioning
confidence: 99%